Genetically Predicted Milk Intake Increased Femoral Neck Bone Mineral Density in Women But Not in Men - Chen, Song; Zheng, Changhua; Chen, Tianlai; Chen, Jinchen; Pan, Yuancheng; Chen, Shunyou (Frontiers in Endocrinology, 2022)
Background: Cow milk contains more calcium, magnesium, potassium, zinc, and phosphorus minerals. For a long time, people have believed that increasing milk intake is beneficial to increase bone density. Many confounding factors can affect milk consumption, and thus the association described to date may not be causal. We explored the causal relationship between genetically predicted milk consumption and Bone Mineral Density (BMD) of the femoral neck and lumbar spine based on large samples using the Mendelian randomization (MR) study. Methods: A genetic instrument used for evaluating milk consumption is rs4988235, a locus located at 13,910 base pairs upstream of the LCT gene. A Mendelian randomization (MR) analysis was conducted to study the effect of selected single nucleotide polymorphisms (SNPs) and BMD. The summary-levels data for BMD of femoral neck and lumbar spine were obtained from two GWAS meta-analysis(‘ Data Release 2012’ and ‘‘Data Release 2015’’ in the GEnetic Factors for OSteoporosis Consortium (GEFOS) ). Results: we found that genetically predicted milk consumption was not associated with FN-BMD( OR 1.007; 95% CI 0.991–1.023; P = 0.385), LS-BMD( OR 1.003; 95% CI 0.983–1.024; P = 0.743) by performing a meta-analysis of several different cohort studies. High levels of genetically predicted milk intake were positively associated with increased FN-BMD in Women. The OR for each additional milk intake increasing allele was 1.032 (95%CI 1.005–1.059; P = 0.014). However, no causal relationship was found between milk consumption and FN-BMD in men (OR 0.996; 95% CI 0.964–1.029; P = 0.839). Genetically predicted milk consumption was not significantly associated with LS-BMD in women(OR 1.017; 95% CI 0.991–1.043; P = 0.198) and men (OR 1.011; 95% CI 0.978–1.045; P = 0.523). Conclusion: Our study found that women who consume more milk have a higher FN-BMD. When studying the effect of milk consumption on bone density in further studies, we need to pay more attention to women.